THE GROWTH OF OIL PALM VARIETIES (ELAEIS GUINEENSIS JACQ.) ON SUBSOIL MEDIA TREATED WITHSEVERAL DOSAGES OF NITROGEN FERTILIZER - Khairani, Siti; Akoeb, Erwin Nyak; Sutarta, Edy Sigit; Sabrina, T. (Universitas Negeri Medan, 2017)
AbstractOilpalmis one of important export commodities performing as the country’s main foreign exchange from the trade of crops.Nitrogen is a limiting factor of plant growth. This study aims to determine: 1) the appropriate dose of absorption of nitrogen and growth in some high yielding varieties of oil palm; 2) the superior varieties of oil palm crops that provide no effect from the nitrogen nutrients and; 3) the interaction between varieties and nitrogen fertilizer on nitrogen nutrient absorption efficiency. This research was conducted in Palm Oil Research Centre at the District of Deli Serdang, the Province of North Sumatra.The research used Factorial Random Block Design with 2 factors. The first factor is varieties (Avros 540, PPKS 239, Simalungun, Langkat and 718PPKS). The second factor is N fertilizer which consists of without N fertilizer, 25% fertilizer recommendation, 50% fertilizer recommendation, 75% fertilizer recommendation and 100% fertilizer recommendation. The results showed that the varieties of oil palm used have different characteristics on plant height, stem diameter and number of leaves. The Simalungun variety was the best variety and its combination with 100% recommendation N was the best result in increasing plant heightof oil palm. Meanwhile the combination with 50% recommendation N was the best result in increasing stem diameter and number of leavesof oil palm.Keywords: oilpalm, nitrogen fertilizer, variety